A Way for better communications among Malaysian professional women towards a sustainable community - Rokis, Rohaiza (2010)
Introduction: This paper explores communication issues between women and non-women dimensions such as men, organisations, systems and policies. Objective: It serves, firstly, to explore women experiences at work in relation to gender communication; and secondly, to suggest ways in promoting better gender communication between women and non-women dimensions for sustainable community at work. Hypothesis: Its stance is that effective communication skills promote sustainable community, particularly in promoting competency, enhancing self-efficacy as well as ceasing stigma perceptions at work. This is because the study takes a basic premise that the non-women dimensions contribute to the professional marginalisation of women at work, as they experience various conflicts at the workplace and home. Conflicts from home such as love for the family and commitment to work always result in extra pressure for them. In addition, the pre-determined external perception embedded in the Asian culture that sees women‘s place fixes at home sometimes add unnecessary obstacles and stress to women. Method, methodology and sample: This paper applies ethnomethodology technique using the talks of experiences of ten women professionals who work at various settings such as universities, public listed companies, ministries and hospitals. Findings: Based on the discourse analysis, this study stresses the importance to develop understanding on the experiences of professional female workers in Malaysia. Conclusion: Effective communication skills in speech and signals at work promote competency, enhance self-efficacy as well as cease stigma perceptions among professional women.